2007
DOI: 10.1111/j.1540-6261.2007.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Executive Financial Incentives and Payout Policy: Firm Responses to the 2003 Dividend Tax Cut

Abstract: We test whether executive stock ownership affects firm payouts using the 2003 dividend tax cut to identify an exogenous change in the after-tax value of dividends. We find that executives with higher ownership were more likely to increase dividends after the tax cut in 2003, whereas no relation is found in periods when the dividend tax rate was higher. Relative to previous years, firms that initiated dividends in 2003 were more likely to reduce repurchases. The stock price reaction to the tax cut suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
134
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(155 citation statements)
references
References 41 publications
14
134
1
Order By: Relevance
“…Dividends tend to be persistent (Goncharov & van Triest 2011;Moser 2007) and PD controls for the change in dividend per share of the previous year. A number of studies found that shares held by employees affect the likelihood that dividends will be paid (Brown, Liang & Weisbenner 2007;Minnick & Rosenthal 2014). Consequently, the model controls for the percentage of common shares held by employees (EMP).…”
Section: Methodsmentioning
confidence: 99%
“…Dividends tend to be persistent (Goncharov & van Triest 2011;Moser 2007) and PD controls for the change in dividend per share of the previous year. A number of studies found that shares held by employees affect the likelihood that dividends will be paid (Brown, Liang & Weisbenner 2007;Minnick & Rosenthal 2014). Consequently, the model controls for the percentage of common shares held by employees (EMP).…”
Section: Methodsmentioning
confidence: 99%
“…e.g. Lie and Lie (1999), Fenn and Liang (2001), Perez-Gonzalez (2002), Graham and Kumar (2006), Brown et al (2007), Barclay et al (forthcoming) and Hsieh and Wang (2008)). Since Germany underwent a major tax reform in the year 2001 (cf.…”
Section: Tax Regime Effectsmentioning
confidence: 99%
“…For example, Core and Larcker () examine a sample of firms adopting ‘target ownership plans’ and find that the required increases in managerial ownership lead to improvements in the firm's operating performance. Fenn and Liang () and Brown et al () find that executives with higher ownership are more likely to increase dividends, but Fenn and Liang () also show that management stock options are negatively (positively) related to dividends (repurchases). Denis et al () suggest that managerial ownership creates incentives for managers to pursue value‐increasing investments and therefore constrains business diversification and avoids value destruction.…”
Section: Empirical Evidence On Executive Compensationmentioning
confidence: 99%
“…While one may interpret this evidence as empirical validity of the widespread misuse of CEO compensation, an alternative is that the endogeneity of compensation arrangements makes it extremely difficult to interpret any observed relation between CEO compensation and corporate outcomes as evidence of a causal effect. A response to such a challenge in recent research is to identify a natural experiment, such as a regulatory change and unexpected ‘shock’ to the economy (see, for example, Brown et al , ; Gormley et al , ).…”
Section: Empirical Evidence On Executive Compensationmentioning
confidence: 99%